2022
DOI: 10.54910/sabrao2022.54.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Stevia (Stevia Rebaudiana B.) Genotypes Assessment for Leaf Yield Stability Through Genotype by Environment Interactions, Ammi, and Gge Biplot Analyses

Abstract: Multilocation testing plays a vital role in the release of new high-yielding cultivars of stevia (Stevia rebaudiana B.) in Indonesia. In stevia, the leaf yield potential demonstrates an important characteristic for superior genotype selection. The study sought to identify the effects of genotype by environment interactions (GEI) on stevia yield and select the genotypes with stable yield resulting from radiation and hybridization through AMMI and GGE biplot analyses under three growing environments. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Similar results were found in Adham et al, Alizadeh et al, and Ansarifard et al that the environment accounted for most of the variance [16,35,36]. Additionally, the GEI effect is largely a response to environmental factors, not genotypic factors [37]; thus, the significant GEI factors demonstrated that the use of AMMI and the GGE biplot was appropriate in yield evaluation [38].…”
Section: Yield Performance Evaluationsupporting
confidence: 85%
“…Similar results were found in Adham et al, Alizadeh et al, and Ansarifard et al that the environment accounted for most of the variance [16,35,36]. Additionally, the GEI effect is largely a response to environmental factors, not genotypic factors [37]; thus, the significant GEI factors demonstrated that the use of AMMI and the GGE biplot was appropriate in yield evaluation [38].…”
Section: Yield Performance Evaluationsupporting
confidence: 85%
“…According to Jamshidmoghaddam [ 48 ], the large of variation in the growth environment that affects crop yields causes the appearance of GEIs. Some researchers reported the comparison of the GGE biplot and AMMI measurements were useful for the evaluation of GEIs under multi-locations [ 15 , 21 , [49] , [50] , [51] ].…”
Section: Discussionmentioning
confidence: 99%
“…Each stability measure has its own advantages and disadvantages in explaining the phenomenon of the GEIs. Therefore, most breeding programs now integrate some of statistical measurements [ 10 , 13 , 20 , 21 ]. Planting the stable and high yield genotype in a diverse environments is one approach to increase sweet potato production in the country.…”
Section: Introductionmentioning
confidence: 99%
“…The Bandung dry field and Sumedang dry field environments are Type III environments because they have long vectors but large angles to the abscissa. These two environments should not be to select superior genotypes but can be used to select adapted or region-specific genotypes (Mustamu et al 2018;Amien et al 2022). This means that these environments will produce good yields for certain genotypes.…”
Section: Discussionmentioning
confidence: 99%